Effect of moisture conservation techniques on almond (Prunus dulcis) productivity under rainfed conditions - KUMAR, DINESH; SRIVASTAVA, K K; SINGH, D B (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted to study the effect of moisture conservation techniques on productivity enhancement in almond (Prunus dulcis Mill) during 2010-11 to 2012-13 at Srinagar, Jammu and Kashmir. Treatment sincluded five water harvesting techniques, viz. half-moon (W1), full-moon (W2), cup and plate (W3), trench (W4) and control (W5) and three mulch materials, viz. plastic mulch (M1), organic mulch (M2) and control (M3) were laid out in factorial randomized block design with three replication. The experimental results revealed that maximum mean trunk cross sectional area (266.82 cm2), nut yield (5.37 kg/tree), productivity efficiency (19.47 g/cm2 TCSA) and soil moisture content (13.48%) were recorded in full moon water harvesting technique. Among mulch material, plastic mulch found better in respect to TCSA (255.59 cm2), nut yield (4.99 kg/tree), productivity efficiency (18.88 g/cm2 TCSA) and soil moisture content (12.86%) compared to other treatments. The combined effect of water harvesting and mulching indicated that maximum TCSA (270.48 cm2), nut yield (5.82 kg/tree), productivity efficiency (20.92 g/cm2 TCSA) and soil moisture (13.98 %) were recorded in full moon water harvesting + plastic mulch in almond cultivar Non Pareil under rainfed conditions of north west Himalayan regions of India.